Breast cancer-related mortality in Central and Eastern Europe: years of life lost and productivity costs. (31st December 2023) - Bencina, Goran; Chami, Nour; Hughes, Robert; Weston, Georgie; Baxter, Carl; Maciejczyk, Adam; Popovic, Lazar; Karamousouli, Eugenia; Salomonsson, Stina
Abstract: Background: Breast cancer (BC) poses a public health challenge as the most commonly diagnosed cancer among women globally. While BC mortality has declined across Europe in the past three decades, an opposite trend has been reported in some transitional European countries. This analysis estimates the mortality burden and the cost of lost productivity due to BC deaths in nine Central and Eastern Europe (CEE) countries: Bulgaria, Croatia, Czech Republic, Hungary, Poland, Romania, Serbia, Slovakia, and Slovenia, that have defied the favorable cancer mortality trends. These estimates may provide relevant evidence to aid decision-makers in the prioritization of BC-targeted policies. Methods: The human capital approach (HCA) was used to estimate years of life lost (YLL) and productivity losses due to premature death from BC (ICD-10 code: C50 Malignant neoplasm of breast). YLL and present value of future lost productivity (PVFLP) were calculated using age and gender-specific mortality, wages, and employment rates. Data were sourced from the World Health Organization (WHO), Eurostat, and the World Bank. Results: In 2019, there were 19, 726 BC deaths in the nine CEE countries. This study estimated BC deaths resulted in 267, 184 YLL. Annual PVFLP was estimated to be €85 M in Poland, €46 M in Romania, €39 M in Hungary, €21 M in Slovakia, €18 M in Serbia, €16 M in Czech Republic, €15 M in Bulgaria, €13 M in Croatia, and €7 M in Slovenia. Conclusion: Premature death from BC leads to substantial YLL and productivity losses. Lost productivity costs due to premature BC-related mortality exceeded €259 million in 2019 alone. The data modeled provide important evidence toward resource allocation priorities for BC prevention, screening, and treatment that could potentially decrease productivity losses. Careful consideration should be given to BC-specific policies, such as surveillance programs and the availability of new treatments in CEE countries to decrease the medical and financial burden of the disease.